Q: 5x - 11 -36

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5x + 36 = x Subtract x from both sides: 4x + 36 = 0 Subtract 36 from both sides: 4x = -36 Divide both sides by 4: x = -9

There is a formula for the "difference of squares." In this case, the answer is (5x - 6)(5x + 6)

3+15

12x = 36

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "divided by", "equals".There is no symbol between 5x and y.

Related questions

this a first degree equation. Therefore, 5x + 8 = x - 36 First take likely terms in one side of the equation and independent terms in the other side. 5x - x = -36 - 8 checking the result: 5x(-11) + 8 = -11 -36 4x = -44 -55 + 8 = -11 -36 x = -44/4 so, -47= -47 x = -11 x = -11 is the correct answer

5x-x=36 4x=36 x=36/4 x=9

sorry i am not sure but i dont think it has an answer If this equation is: x^2 - 36 = 5x, then: x^2 - 36 = 5x subtract 5x to both sides; x^2 - 5x - 36 = 0 Factor; (x + 4)(x - 9) = 0 x + 4 = 0 or x - 9 = 0 x = -4 or x = 9

When factored it is: (x-9)(x+4)

(6 - 5x)(6 - 5x)

If you mean (5x+3)2 = 36... 5x+3 must equal 6 so - 5x has to equal 3 - therefore x = 0.6

x2-5x-36 = (x-9(x+4) when factored

(5x - 6)(5x + 6)

5x-2y=11 -2y=-5x+11 y=(5/2)x - 11/2 Slope is 5/2

yes there is.-5x+1=-10-5x=-11-x=-11/5x=11/5

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

(5x+4)(9x+9) FOIL First (5x*9x=45x**2) Outside (5x*9=45x) Inside (4*9x=36x) Last (4*9=36) 45x**2+45x+36x+36 45x**2+81x+36 9(5x**2+9x+4x)